EVALUASI KESESUAIAN LAHAN PADI GOGO PADA TIGA KAWASAN AGROEKOSISTEM DI KABUPATEN JAYAWIJAYA - Anti Uni Mahanani; Sumiyati Tuhuteru; Totok Agung Dwi Haryanto; Muhammad Rif'an (Jurnal Tanah dan Sumberdaya Lahan, 2020)
The people of Papua currently tend to consume rice continuously every year compared to local food. The purpose of this study was to determine the adaptive and high yielding upland rice varieties in three agroecosystem zones of Jayawijaya Regency. Testing of five varieties has been carried out in three agroecosystem zones in Jayawijaya Regency, namely zone 1 with an altitude of 1882 m above sea level (Walelagama District), zone 2 with an altitude of 2145 m above sea level (Kurulu District), and zone 3 with an altitude of 2653 m above sea level (Sogokmo District). The results showed adaptive Wamena Local (Moai) varieties growing in the three agroecosystem areas, which were seen in the parameters of plant height and number of leaves, followed by INPAGO INPARI 28 varieties. Meanwhile, in the production parameters achieved, INPAGO INPARI 28 varieties produced the highest panicles and grains in Walelagama District at 124.33 panicles and 10.62 t grains ha-1. Whereas in the Kurulu District (Zones 1 and 2) were 124.33 panicles and 3.53 t grains ha-1. The Sogokmo District was shown by INPAGO 9 variety (86.00 panicles and 2.97 t grains ha-1).